THE USE OF INFORMATION TECHNOLOGY IN THE TEACHING OF PHYSICAL EDUCATION AND SPORTS - Inomov Faxriddin Urmonjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article examines the possibilities of using information technology in teaching physical education at a university. Remote methods make it possible to receive consultations from a teacher (coach) at any convenient time, no physical presence in the educational institution is required. Remote technologies expand the possibilities of effective physical education for young people with special physical development.